Tropical fruits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Tropical fruits ISBN 0 85199 254 4, 1998. 445 pp. British Pounds 30 (US $55, only in the Americas) -